Synergistic remediation of continuous cropping obstacles in facility agriculture: insights from the Stropharia rugosoannulata-Ornamental Sunflower Rotation System - Lu, Jia; Chen, Yan; Yan, Jing; Ye, Huiqing; Ying, Xuebin; Zhou, Xiaohua; Yao, Fangjie; Zhou, Zufa (Frontiers in Microbiology, 2025)
Continuous cropping in facility agriculture induces severe soil degradation through acidification, nutrient imbalance, and pathogen accumulation, posing a significant threat to agricultural sustainability; to address this challenge, we developed an innovative Stropharia rugosoannulata-Ornamental Sunflower Rotation System (SR-OS2) incorporating spent mushroom substrate (SMS) and investigated its remediation mechanisms through integrated approaches including soil physicochemical analysis, extracellular enzyme assays, high-throughput sequencing (16S/ITS), co-occurrence network analysis, and Partial Least Squares Path Modeling (PLS-PM). The SR-OS2 system significantly enhanced soil properties by increasing pH (+0.57 units), decreasing electrical conductivity (−37.56%), and boosting available phosphorus (+84.2%), while also shifting microbial communities toward bacterial dominance with a 37.4% increase in bacterial Chao1 diversity and a 39.1% decrease in fungal diversity, alongside strengthened bacterial connectivity (+42%) and reduced fungal modularity in co-occurrence networks. Enzyme stoichiometry further revealed alleviated nitrogen limitation (vector angle: 27.2°–30.9°), and PLS-PM identified dual remediation pathways—a dominant biological pathway (β = 0.92) and a physicochemical pathway (β = −0.501); these improvements collectively demonstrate that the SR-OS2 system synergistically restores soil microecological functions, providing a sustainable paradigm for agricultural waste valorization and effective management of continuous cropping obstacles.